Methodological Approaches to the Study of the Management of the Development of Education in the Sphere of Physical Culture and Sport in Poland - Oleksandr Mozolev (Pedagogical Discourse, 2016)
In the article the author revealed the methodological approaches to the study education development management system of in the sphere of physical culture and sport in Poland. Installed tools and methodology of management systems research have been established. Substantially-procedural scheme of the research and types of scientific analysis that are used by the author have been disclosed. Research methods and the scope of their application have been defined.It is specified that implementation of the set of work task is based on a systematic, integration, structural-functional, multi-methodological, dialectal, situational, innovative, normative, administrative, quantitative and behavioral approaches applying three groups of methods: aristotelian, general scientific and specific. It is found that the management theory identifies a systemic approach, as the most universal method of research to study of the state, organization, structure, interaction of various aspects of the functioning system. Author identified that the substantially-procedural scheme of research involves the use of the following scientific analysis: problematic, systematic, causal, praxeological, axiological, program-target, situational, predictive and a recommendative. The entire research process involves the integrated use of aristotelian research methods, namely: analysis, synthesis, induction, deduction, analogy, axiomatic method, method of formalization, abstraction, generalization, from abstract to the concrete, etc. Historical, comparative law methods were used in the study to examine the status of the development of the problem in the scientific literature and the works of Polish scholars. Mathematical-statistical methods are used in order to define the resource, personnel, material - technical and medical support to the development of education in the sphere of physical culture and sport of Poland. Financial analysis is used to establish the level of funding for the development of education in the sphere of physical culture and sport of Poland, methods of mathematical modeling used for prognostic modeling of investigated processes.Key words: methodology, management, methods, education, physical culture.